Multiparticle correlations and higher order harmonics in pPbcollisions at√sNN=8.16 TeV - Wang, Quan; Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Md. Ali, Mohd. Adli (Elsevier B.V., 2019)
The elliptic and higher-order azimuthal anisotropy Fourier harmonics (v n ) are obtained for pPb collisions at s NN =8.16TeV over a wide range of event multiplicities based on multiparticle correlations. The data were collected by the CMS experiment during the 2016 LHC run. A sample of peripheral PbPb collisions at s NN =5.02TeV covering a similar range of event multiplicities to the pPb results is also analyzed for comparison. The ratios of different harmonic moments are obtained for both v 2 and v 3 with high precision, which allows a direct comparison to theoretical predictions assuming a hydrodynamic evolution of the created medium with initial-state density fluctuations, particularly probing the non-Gaussian nature of initial-state fluctuations in small collision systems. The presented results provide crucial insights into the origin of collective long-range correlations observed in small collision systems.